Upaya Meningkatkan Kemampuan Pengenalan Konsep Bilangan Pada Anak Kelompok A Dengan Metode Bermain Plastisin - Rakhel Ruth Berkati Zega (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2022)
This research is motivated by the low ability to recognize number concepts in group A children, including not being able to recognize number symbols, not being able to count with objects and not being able to connect/pair objects with number symbols. This study aims to improve the ability to recognize the concept of numbers in children with the method of playing with plasticine at Kanisius Cungkup Kindergarten, Salatiga. The type of research is Classroom Action Research and the subject of this research is group A students totaling 12 children, with 4 boys and 8 girls. Data collection techniques through observation and documentation with qualitative descriptive data analysis. The results showed that there was an increase in the introduction of the concept of children's numbers. In the first cycle, the percentage of indicators mentioning numbers 1-10 is 100%, numbering objects 1-10 is 83.3%, indicators recognizing symbols for numbers 1-10 are 66.6%. In cycle II, the percentage of indicators recognizing the symbols of numbers 1-10 is 91.6%, matching numbers with number symbols is 83.3%.AbstrakPenelitian dilatarbelakangi oleh masih rendahnya kemampuan pengenalan konsep bilangan pada anak kelompok A, diantaranya belum mampu mengenal lambang bilangan, belum mampu berhitung dengan benda-benda dan belum mampu menghubungkan/memasangkan benda-benda dengan lambang bilangan. Penelitian ini bertujuan untuk meningkatkan kemampuan pengenalan konsep bilangan pada anak dengan metode bermain plastisin di TK Kanisius Cungkup Salatiga. Jenis penelitian yaitu Penelitian Tindakan Kelas dan subjek penelitian ini adalah siswa kelompok A berjumlah 12 anak, dengan 4 anak laki-laki dan 8 anak perempuan. Teknik pengumpulan data melalui observasi dan dokumentasi dengan analisis data deskriptif kualitatif. Hasil penelitian menunjukkan bahwa terjadi peningkatan pada pengenalan konsep bilangan anak. Pada siklus I persentase indikator menyebutkan bilangan 1-10 sebesar 100%, membilang banyak benda 1-10 sebesar 83,3%, indikator mengenal lambang bilangan 1-10 yaitu 66,6%. Pada siklus II persentase indikator mengenal lambang bilangan 1-10 yaitu 91,6%, mencocokkan bilangan dengan lambang bilangan yaitu 83,3%.